2015
DOI: 10.1111/jam.12868
|View full text |Cite
|
Sign up to set email alerts
|

Autumnal increase in proportion of toxic Microcystis in Lake Taihu depends more on temperature adaptability than on effects of toxigenicity

Abstract: This is the first report that the dynamics of toxic/nontoxic Microcystis was investigated in combination with characterizations of multiple isolated strains. The results are useful in understanding Microcystis genotype succession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These results are consistent with previous research which found that the season succession of the Microcystis population in Lake Taihu was dominated by a few genotypes despite there being over 20 genotypes have been identified. 59 Therefore, we propose that future efforts to suppress harmful cyanobacterial blooms in Lake Chaohu should focus on specific strains rather than at the species or above-species level.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with previous research which found that the season succession of the Microcystis population in Lake Taihu was dominated by a few genotypes despite there being over 20 genotypes have been identified. 59 Therefore, we propose that future efforts to suppress harmful cyanobacterial blooms in Lake Chaohu should focus on specific strains rather than at the species or above-species level.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al . (2015) proposed that the rapid increase and decrease in the proportions of toxic strains in Microcystis populations in Lake Taihu were associated with temperature adaptability rather than toxigenicity. Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are plenty of studies that have focused on the relationships between toxic cyanobacteria and environmental variables. These include studies that have investigated the relationship between toxic blooms and Microcystis species colony sizes (Kurmayer et al ., 2003), nitrate (Yoshida et al ., 2007), NO x and NH 4 (Ha et al ., 2009), phosphorus (Rinta‐Kanto et al ., 2009; Davis et al ., 2010) and water temperature (Joung et al ., 2011; Hu et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was extracted as described previously ( Hu et al, 2015 ). Briefly, cells were digested with proteinase K (Thermo Fisher Scientific, United States).…”
Section: Methodsmentioning
confidence: 99%